Integration and Pricing Efficiency of Rice Market - Raj Singh, Bishwa Bandhu (1999)
This study Investigated performance of rice market in Nepal by analysing interdependence of prices (market integration) and efficiency of arbitrage (pricing efficiency) among the regional wholesale markets An Integrated approach to the analysis of performance of the market system was adopted The cointegration-based Johansen's Vector Error Correction Model (VECM) was used for analysis of nature of interdependence of prices in the regional markets to infer on integration Switching Regimes Model (SRM) was used to evaluate efficiency of arbitrage between market regions related in direct trade to infer on pricing efficiency of the market system The analysis results for market Integration and pricing efficiency were interpreted In relation to the structural and behavioral characteristics of the market system being Investigated through the rapid appraisal market survey The evaluation of results from estimation of the VECM lend support to the hypothesis that regional markets for rice in Nepal are integrated to form a single market area With Kathmandu as the central market Price shocks m the central market gets quickly transmitted to the regional markets However, the results from estimation of the SRM for the five market pairs provided statistical evidence of violation of efficient arbitrage conditions This supports the hypothesis that the integrated rice market in the country is not efficient m arbitrage sense Consideration of behavioral characteristics of the market indicated inefficient integration of the market regions could be due to lack of adequate institutional infrastructure in the market that provided the large millers and traders to enjoy some degree of market power The study indicates that physical facilities in the market are necessary for integration of the market, but these alone are not sufficient for a market system to be efficient with expansion of the market through economic integration, need for provision of appropriate institutional Infrastructure In the form of public and private order institutions arises The government needs to play a crucial role in providing institutional infrastructures to make the market more competitive, efficient and equitable.